O coordenador pedagógico na educação pública municipal de Feira de Santana-BA: implicações do desenvolvimento da práxis em escolas de educação infantil (2005-2021) - Santos, Patrícia Amorim Bispo dos (2022)
This research presents as its central theme the pedagogical coordinator in municipal public education in Feira de Santana and the implications of the development of praxis in early childhood education schools. Answers were sought for the following research question: how does the pedagogical coordinator of the municipal public education of Feira de Santana develop his practice in early childhood education schools? To investigate this issue, the general objective was to analyze the praxis of the pedagogical coordinator as the professional who promotes changes in the school and in the community, based on the social, political and pedagogical determinants of municipal public education in Feira de Santana in early childhood education schools. Aiming at reaching the general objective, the following specific objectives were listed: to analyze the historical, political, pedagogical and legal trajectory of the constitution of the Pedagogical Coordinator at national and local levels; analyze the relationships established between theory and practice in the performance of pedagogical coordinators in municipal schools for children's education in Feira de Santana; reflect on the concept of praxis relating to the actions of the pedagogical coordinator. The research was configured within the critical-dialectical epistemological matrix and the qualitative approach, having as a procedure the documental and bibliographic analysis using the questionnaire (Google Forms forms) and documental analysis as data collection instruments, with the participation of 8 (eight) pedagogical coordinators who work in exclusive early childhood education schools. The historical outline of the research was delimited for the period of 2005, the year when the function of pedagogical coordinator officially began in Feira de Santana, until the year 2021, when data collection for the research began. The concept of praxis was discussed in light of the assumptions of historical and dialectical materialism, having as reference the philosopher Vázquez (2011), the educator Freire (1987, 2002) and the economist, philosopher, sociologist and historian Marx (2000, 2007). By presenting the collected data and their analysis, we sought to identify how the pedagogical coordinator develops the praxis in municipal public schools for early childhood education in Feira de Santana. The results of the investigation show that the pedagogical coordinator promotes changes in the school and in the community through his/her praxis, organizing real reflective actions, leaving the theoretical, imaginary plan and implementing their actions in effective, meaningful and transforming practices. Therefore, a coordinator committed to a political proposal and not to the fulfillment of an alienated and repetitive role, has the possibility of transforming the school in the exercise of its function, making practice effective.